Strategies of English Expressions of Gratitude Used by Yemeni Male Speakers in Male-Male and Male-Female Interactions - Sari, Bushra; Al-Marrani, Yahya Mohammed (International Journal of Language and Literary Studies, 2024)
This study aims to identify the types of English expressions of gratitude that are employed by Yemeni Male Speakers in Male-Male and Male-Female interactions. The participants of the study consisted of 230 students (115 males and 115 females) from Sana’a University. The data of the study were collected by using a Discourse Completion Test (DCT) questionnaire. The results of the study showed that the participants employed different types of English expressions of gratitude in different gratitude situations, but "bald thanking or using the word "thank" was the most frequently used strategy by Yemeni male speakers in male-male and male-female interactions. The results also indicated that there were similarities and few differences in terms of the frequencies, percentages and the type of strategies used by the participants in all situations.